Online peer support groups for individuals with Type 2 diabetes mellitus: an exploratory mixed-methods study - Muslihi, Abdulrahman (2024)
Background: Type 2 diabetes mellitus (T2DM) is a disorder that is associated with long-term complications that may lead to serious consequences, including amputation and mortality. T2DM demands fundamental life changes, and people newly diagnosed with T2DM (PND-T2DM) may face challenges adjusting to this new reality, whereby they can benefit from ongoing social support. Peer groups providing social support are becoming increasingly popular in modern health and social care, as peers are often better able to offer support and empathy than professionals, as well as to recognise a person’s particular situation and challenges. However, there are challenges in finding peers with T2DM and joining a secure environment for exchanging peer support. Online tools can facilitate the creation of peer support groups, allowing individuals with T2DM to connect with peers more safely and conveniently. Within these groups, individuals can exchange experiences, provide information, and motivation, ultimately resulting in overcoming challenges and adopting healthier lifestyles. Aims and objectives: This PhD thesis aims to design an online peer-to-peer support group (OPSG) intervention for PND-T2DM in Jazan, Saudi Arabia. Method: Within the pragmatic paradigm, and following the Medical Research Council framework, this study was informed by the Social Support Theory and the Unified Theory of Acceptance and Use of Technology to design an OPSG intervention for PND-T2DM in Jazan. The study utilised an exploratory mixed-methods design. Semi-structured interviews (Phase 1) explored the perspectives of 15 individuals regarding OPSGs in-depth, and sequentially a modified Delphi technique (Phase 2) assessed the level of agreement among a panel of 33 healthcare practitioners (HCPs) regarding the design of an OPSG intervention for PND-T2DM. Data from Phase 1 was recorded, fully transcribed and translated, and thematically analysed. In Phase 2, statements were created based on Phase 1 data, and were then refined through iterative rounds. Findings: Interviews with PND-T2DM in Phase 1 revealed four main themes: Patients’ Needs for OPSGs, OPSG-Receptivity, OPSG-Benefits, and OPSG-Development. This phase identified the challenges that those individuals faced in managing diabetes, encompassing the physical, emotional, and behavioural dimensions, and highlighted OPSGs’ potential to address related issues. Although many participants were not familiar with OPSGs, most expressed interest in joining, attracted by the perceived benefits. When designing OPSG interventions, it is essential to consider OPSG-Developmental components, including individuals with similar characteristics and HCP-diagnosed with T2DM, co-facilitators, 20-50 members, gender diversity, the WhatsApp platform, peer interactions (focusing on diet, exercise, and medications), and group activities (like goal-setting and counselling services). The findings offer valuable insights into the design of OPSGs and directed the next phase of the study. Consensus was reached on 33 statements within two dimensions over two rounds. The subsequent phase showed that HCPs engaging in OPSGs can offer benefits, regardless of their T2DM diagnosis, and PND-T2DM can benefit from joining single- or multi-gender OPSGs, as long as all members agree to follow the group’s policies. Members of OPSG have the chance to decide their involvement in discussions concerning negative and sexual experiences. Together, the thesis findings were incorporated consolidated and presented concisely and practically, using a Logic Model, which offers a thorough explanation of the intervention’s mechanism and can be utilised in future studies to assess its feasibility. Conclusion: This thesis fills a research gap by designing a personalised support system for PND-T2DM, integrating their viewpoints and healthcare expert feedback. The OPSG intervention can help to provide a viable solution for PND-T2DM in the context to exchange social support, resulting in managing daily self-care challenges. The OPSG intervention enhances the healthcare system by focusing on patient-centred care, enhancing interactions, and offering social support to individuals requiring assistance.